How FaaS with DBaaS performs in different regions: an evaluation by the Orama Framework - Carvalho, Leonardo Rebouças de; Kamienski, Bruno; Araujo, Aleteia (Anais do Simpósio em Sistemas Computacionais de Alto Desempenho (SSCAD); 2023: Anais do XXIV Simpósio em Sistemas Computacionais de Alto Desempenho, 2023)
Studies indicate that cloud services based on the serverless paradigm, such as Function-as-a-Service (FaaS) should become the main mechanisms of the next generation of cloud computing. Given this perspective, public cloud providers have made efforts to expand the coverage of their services in order to meet this need. However, the effort needed to maintain equivalence between different regions highlights the importance of studying the behavior of FaaS environments in different regions of providers. This work presents a study aided by the Orama framework in order to evaluate the performance of the main FaaS integrated with Database-as-a-Service (DBaaS) services in five regions spread across the globe. The results indicate that the Alibaba provider was able to guarantee good equivalence between its regions, in addition to a lower average execution time. AWS and GCP had similar results, although the error rate on AWS was the highest on average. Azure, on the other hand, had the worst performance, with the highest average execution time, in addition to significant failure rates.